Homework in the primary school: teachers and students' perception. - Lopes, Mónica (2022)
Homework is some of the most widespread, but also controversial, strategy used in the first school years. Homework is perceived differently by teachers and students. In this work, primary school teachers and students’ perception on homework and its relation with some variables was studied. For that, a descriptive, correlational, cross-sectional survey was performed on 17 teachers and 282 students from year 5 and 6 of Viseu. Data analysis shows that all teachers give homework regularly and they consider it important to learning’s consolidation and performance’s improvement. Assigned homework mostly covers Mathematic and Portuguese curricular units and the majority of teachers do not give any type of reward for homework completion. Concerning students, was observed that the majority of them likes to do homework and performs it at home with help. When questioned about the possibility of not performing homework there was an association between the decision to do homework and the enjoyment of doing it, as well as with the time available to do other activities. On the other hand, the possibility of not performing homework was not associated with the time spent doing homework. Even though most students enjoy doing homework, they wish they included other areas. For these reasons, it is important to adjust the quantity of homework, as well as to diversify it, both in typology and aims, so that the interest and needs of students are met.